The African Framework for Intra-Regional Trade Between Continental Aspirations and the Reality of Structural Marginalization: A Critical Analytical Study of the African Continental Free Trade Area (AfCFTA) and Economic Integration Prospects (Journal of Informatics Education and Research, 2026)
This analytical study addresses the problematic of "trade marginalization" plaguing the African continent, clearly manifested in the negligible volume of intra-regional trade compared to other global economic blocs such as the European Union and Asia. The paper aims to deconstruct the structural architecture of the African economy inherited from the colonial era and analyze the effectiveness of modern institutional frameworks, primarily the African Continental Free Trade Area (AfCFTA) agreement, in addressing this structural imbalance. Utilizing a descriptive-analytical and comparative approach, and based on the latest statistical data for 2022-2023 issued by the African Export-Import Bank (Afreximbank) and the Economic Commission for Africa (UNECA), the study concludes that removing tariff barriers alone will not be sufficient to break the cycle of marginalization. The results reveal that non-tariff barriers, weak logistical infrastructure, and the absence of regional value chains represent the true obstacles to integration. Furthermore, the paper critically discusses the potential risks of major economies (Egypt, Nigeria, South Africa) dominating trade gains, which could reproduce marginalization internally. In conclusion, the study recommends adopting integrative industrialization policies, accelerating the digital transformation of trade, and activating the Pan-African Payment and Settlement System to decouple from foreign currencies.